Optimisation of microparticle formulations for IL-4 delivery for macrophage modulation in spinal cord injury - Stening, Jasmine Z. (2020)
Spinal cord injury currently lacks treatment capable of restoring limb function and sensation. Current strategies, using pharmaceuticals and physiotherapy, focus on alleviating the high inflammatory environment triggered as a result of injury. These often result in adverse side effects and no rehabilitation. The discovery of macrophage phenotypes and their roles in inflammation within spinal cord injury has provided a new target for treatment development. Understanding macrophage behaviour and the roles of their sub-phenotypes has suggested a method for controlling inflammation by modulation towards a pro-immunoregulatory subgroup using cytokine interleukin 4 (IL-4). The hypothesis was that sustained delivery of IL-4 could modulate macrophage phenotype and provide resolution in the context of inflammation in spinal cord injury.